(3fXGe GdahGFO hJbQjH GdeQGO ddQGFOs - (3LYaQ Hf CMeO Hf YHO GdSdGe Hf CHj jMji UGYO, TeS GdOjf CHh GdaVds
(3ChdgG (B:s
(3CeG HYO MeO Gddg JYGdi Ydi LRjd fhGdg hGdKfGA Ydjg ce jSJMbg dYXeJg hLdGdg s
(3BNQgG (B:s
(3Ke GdNHQ Ef UM jOd Ydi GdoeJbOe Ydi GdcHGFQ dGjONd GdLfI hEfeG jONdgG ef JGH ef Pdc hELJfHgG GfJgi cJGH fXe GdahGFO hJbQjH GdeQGO ddQGFO s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs